Implementasi Pelatihan Keterampilan Penataan Rambut pada Remaja Karang Taruna di Candi Sidoarjo - Arif, Desy Syafida; Maspiyah, Maspiyah (Journal of Beauty and Cosmetology (JBC), 2020)
Teenagers are a national asset. Their potential needs to be developed by providing skills training. One of the skills needed today is hair styling services. The purpose of this study are: (1) knowing the implementation of hair styling skills training and (2) knowing the results of hair styling skills training. This research was pre-experimental design with one-case study. The subject of this research is the teenage girls of Gelam village, Sidoarjo.  Data collection with observation and skills tests. The research location was in Gelam village, Sidoarjo on April 2020. The results of the research revealed that the implementation of training, hair styling went very well from the introduction, implementation, evaluation and packing. Active and enthusiastic participants in following the training. Hair styling skills are assessed with indicators of hair partitioning, shaking, curling, hair styling, neatness, and excellent results. This training contributed to participants in two aspects, namely knowledge and skills improvement.